Study protocol for the multicentre cohorts of Zika virus infection in pregnant women, infants, and acute clinical cases in Latin America and the Caribbean: the ZIKAlliance consortium - Avelino-Silva, Vivian I.; Rosenberger, Kerstin; Pohl, Moritz; Jänisch, Thomas; Morales, Ivonne; Tobian, Frank; Uhlmann, Lorenz; Schretzmann, Julius Leonard; Leege, Annika (BMC infectious diseases, 2019)
The European Commission (EC) Horizon 2020 (H2020)-funded ZIKAlliance Consortium designed a multicentre study including pregnant women (PW), children (CH) and natural history (NH) cohorts. Clinical sites were selected over a wide geographic range within Latin America and the Caribbean, taking into account the dynamic course of the ZIKV epidemic.